Construction management analysis of time management in residential house construction of samarinda - Zunaidah, Umi; Kawuryan, Renita; Prasetyo, Dimas Rabbani; Aditya, Rangga; Cindy, Cindy; Aisyah, Ridha; Salsabila, Shafa Nadiah (Institute of Computer Science (IOCS), 2024)
The construction services industry in Indonesia is expanding rapidly, necessitating efficient project management to maintain competitiveness. This study analyzes time management in residential construction in Samarinda, using the Critical Path Method (CPM) and Microsoft Project software. The research aims to identify deficiencies in current practices to enhance project efficiency. A quantitative approach was adopted, involving literature review, data collection through field surveys and interviews, and data analysis. Findings reveal that the total construction period is 93 days, with a project duration of 4,900 hours. Weather conditions were a significant factor causing incomplete tasks. Cost analysis indicates total expenses of Rp201,290,412, emphasizing the importance of precise cost management alongside time management. The study concludes that effective use of CPM and Microsoft Project can optimize scheduling, resource allocation, and overall project management. Recommendations include regular critical path reviews and enhanced team communication to mitigate delays and ensure timely project completion